Influence of Brand Image and Celebrity Endorser on Purchase Decisions on Samsung Smartphone Products - Annisa Viaski Handayani; Rif'ah Dwi Astuti; Makmun - Riyanto (JOBS (Jurnal Of Business Studies), 2022)
With the advancement of technology, all activities in society are now easier. One of them is that it is getting easier for people to communicate and exchange data or information using only one device, namely a smartphone. The objective of this research is to analyze the influence of brand image (X1) and celebrity endorser (X2) on purchase decisions (Y) of samsung smartphone products. This research used a multiple linear regression analysis. The primary data used in this research is collected from questionnaire. The population in this study are people who bought Samsung smartphones in Semarang City between 2020 and 2022, whose number is unknown. The amounts of the respondents are 100 who are Samsung smartphone users in Semarang. The analysis tools used were test of validity, reliability test, normality test, heteroscedasticity test, multicollinerity test, linearity test, multiple linear regression, T test, F test, and the coefficient of determination. Based on the calculations using SPSS version 26, the results of this research showed that the regression equation Y = 0,395 + 0,680 X1 + 0,269 X2. In addition, the F test result of 41,637 which was bigger than F table was 3,08. It can be concluded that the model in this study is correct. The T test result the variables brand image (X1) and celebrity endorser (X2) were bigger than T table and had a significance less than level significance of 0,05. So, it can be concluded the brand image (X1) and celebrity endorser (X2) had a positive and significance influence on purchase decisions (Y). The most influence variable is brand image (X1) with the highest regression coefficient of 0,680. The contribution of brand image and celebrity endorser on purchase decisions is 50,5 % while 49,5 % are influenced by other variables that were not described in this research.